Work-Life Balance and Job Satisfaction for Hotel Employees in Delhi NCR, India - Sharma, Vikas (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research delves into the impact of work-life balance practices on the job satisfaction of kitchen professionals working in five-star category hotels situated in Delhi NCR, India. Employing a quantitative approach, data is gathered through surveys involving 300 respondents. Descriptive statistics, correlation analysis, and multiple regressions are harnessed to explore the intricate relationships between work-life balance, job satisfaction, and the overall well-being of employees. The findings underscore the pivotal role of work-life balance in elevating job satisfaction within the dynamic kitchen department of the hotel industry. Furthermore, the study offers practical recommendations for hotel kitchen management to effectively implement work-life balance initiatives